2019
DOI: 10.1101/706507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining chromatin state transitions predicts a network that modulates cell wall remodeling in phosphate-starved rice shoots

Abstract: Phosphorus (P) is an essential plant macronutrient vital to fundamental metabolic processes. Plant-available P is low in most soils, making it a frequent limiter of growth. Declining P reserves for fertilizer production exasperates this agricultural challenge. Plants modulate complex responses to fluctuating P levels via global transcriptional regulatory networks. Although chromatin structure plays a substantial role in controlling gene expression, the chromatin dynamics involved in regulating P homeostasis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Studies in diverse plant species and tissues have investigated genic levels of H3K4me3 in response to a variety of stresses (Foroozani et al, 2019;Jaskiewicz, Conrath, & Peterhänsel, 2011;Kim et al, 2008;Pan et al, 2017;Sokol, Kwiatkowska, Jerzmanowski, & Prymakowska-Bosak, 2007;Tsuji, Saika, Tsutsumi, Hirai, & Nakazono, 2006;van Dijk et al, 2010;Zeng et al, 2019;Zheng et al, 2019). Generally these studies reported positive correlations between H3K4me3 abundance and stress-induced gene expression, further supporting an active role for H3K4me3.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Studies in diverse plant species and tissues have investigated genic levels of H3K4me3 in response to a variety of stresses (Foroozani et al, 2019;Jaskiewicz, Conrath, & Peterhänsel, 2011;Kim et al, 2008;Pan et al, 2017;Sokol, Kwiatkowska, Jerzmanowski, & Prymakowska-Bosak, 2007;Tsuji, Saika, Tsutsumi, Hirai, & Nakazono, 2006;van Dijk et al, 2010;Zeng et al, 2019;Zheng et al, 2019). Generally these studies reported positive correlations between H3K4me3 abundance and stress-induced gene expression, further supporting an active role for H3K4me3.…”
Section: Introductionmentioning
confidence: 94%
“…Because it is enriched in genic regions and correlates with transcript levels, it is considered an active histone mark (Françoise S Howe et al, 2017;Santos-Rosa et al, 2002). However, H3K4me3 dynamics have been associated with not only activation, but also repression of subsets of genes (Clouaire et al, 2012;Foroozani et al, 2019;Françoise S Howe et al, 2017;Lenstra et al, 2011). Unlike its counterpart in yeast, Arabidopsis ATX1 has been shown to play a dual role in transcription (Ding et al, 2011b).…”
Section: Functions Of H3k4me3mentioning
confidence: 99%
See 3 more Smart Citations